Aspiring Geopark Gorontalo: Solusi Persiapan Situs Geologi Untuk Pariwisata Pasca-COVID-19 - Meilinda Lestari Modjo; Krishna Anugrah; Yayu Indriati Arifin (Postgraduate, University of Mataram, 2024)
The Geosite Area of Gorontalo Evaluated Using Quantitative Descriptive Research Method for Tourism Preparedness Post-COVID-19